Artificial Intelligence Approaches for Discovering Functional Gene Expression Patterns in Oncogenic Signaling Pathways - Clifford Lewis; Francis Graham (Computational Intelligence Systems, 2026)
The elucidation of functional gene expression patterns within oncogenic signaling pathways represents a critical frontier in precision oncology, yet the inherent complexity and non-linearity of these biological networks challenge traditional analytical methods. Artificial intelligence, particularly deep learning and probabilistic graphical models, offers a transformative paradigm for discovering latent transcriptional structures that govern tumor initiation, progression, and therapeutic resistance. This paper presents a systems-level examination of how AI methodologies can be systematically deployed to uncover regulatory motifs and pathway dependencies from high-dimensional transcriptomic data. We discuss the architectural trade-offs between interpretable models and black-box predictors, the governance challenges related to data provenance and algorithmic bias, and the infrastructural requirements for integrating AI-driven discoveries into clinical decision support systems. Through a comparative analysis of convolutional neural networks, variational autoencoders, and transformer architectures, we evaluate their respective capacities for capturing both local and global expression patterns. The sustainability and robustness of these models are considered in the context of evolving tumor heterogeneity and batch effects across multi-omic datasets. Policy implications for equitable access to AI-guided therapeutic stratification and the ethical deployment of predictive models in oncology are critically assessed. By framing AI as a socio-technical infrastructure rather than a mere analytical tool, this paper provides a comprehensive roadmap for the responsible integration of computational intelligence into oncogenic pathway research. The findings underscore the necessity of interdisciplinary collaboration among computer scientists, biologists, ethicists, and regulators to ensure that discovered patterns translate into actionable clinical insights.